2022
DOI: 10.1021/acs.jafc.2c02940
|View full text |Cite
|
Sign up to set email alerts
|

miR-143-Mediated Responses to Betaine Supplement Repress Lipogenesis and Hepatic Gluconeogenesis by Targeting MAT1a and MAPK11

Abstract: The liver as the central organ is responsible for lipogenesis, gluconeogenesis and one-carbon metabolism. Methyl donors (e.g., betaine) modulate metabolic homeostasis and gene regulation through one-carbon metabolism. MiR-143 regulates DNA methylation by targeting DNMT3A, thereby suggesting that this miRNA participates in one-carbon metabolic pathways. However, the effect and mechanism that regulate glucose and lipid metabolism via the methyl group metabolism pathway remain elusive. In this study, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that genomic deletion of miR-143/145 will not lead to obvious developmental defects, and the overexpression of miR-143 in BAT and liver also does not affect the development of mice [ 42 , 43 , 44 ]. Notably, our published data show that cold exposure stimulates stronger body temperature in miR-143KO mice [ 28 ], indicating that miR-143 may be involved in cold-induced thermogenesis. Therefore, we speculate that miR-143 in adipose tissue acts as a stress miRNA upon metabolic challenge just like miR-21 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that genomic deletion of miR-143/145 will not lead to obvious developmental defects, and the overexpression of miR-143 in BAT and liver also does not affect the development of mice [ 42 , 43 , 44 ]. Notably, our published data show that cold exposure stimulates stronger body temperature in miR-143KO mice [ 28 ], indicating that miR-143 may be involved in cold-induced thermogenesis. Therefore, we speculate that miR-143 in adipose tissue acts as a stress miRNA upon metabolic challenge just like miR-21 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR-143 during obesity remains obscure, and still needs further investigation. More importantly, our published data show that cold exposure stimulates stronger body temperature in miR-143 knockout (KO) mice, indicating that miR-143 may be involved in cold-induced thermogenesis [ 28 ]. However, the function and mechanisms of miR-143 in BAT are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the miRNAs in the BAT is crucial in regulating the pathways that control a range of processes, including adipocyte differentiation, adipogenesis, and thermogenesis [23,24]. As reported, miR-143 is highly expressed in the white adipose tissue (WAT) and BAT [25,26], and miR-143 knockout (KO) mice exhibited stronger ability to maintain body temperature under cold exposure [27], and can effectively resist diet-induced obesity by promoting BAT thermogenesis and inhibiting WAT adipogenesis [28]. More importantly, miR-143 may be involved in the response of adipocytes to obesity-induced macrophage infiltration and cytokines secretion, as treatment of TNFα for 24 h to differentiated 3T3-L1 adipocytes reduced the expression of miR-143 [29].…”
Section: Introductionmentioning
confidence: 95%
“…The overexpression of miR-143 targets an oxysterol-binding protein-related protein (ORP8), leading to its downregulation and impairing insulin-induced AKT activation in obesity-associated diabetes [ 99 ]. miR-143 also directly targets mitogen-activated protein kinase 11 (MAPK11), which impairs gluconeogenesis by two of the involved proteins, phosphoenolpyruvate carboxykinase 1 (PCK1) and glucose-6-phosphatase catalytic (G6PC), in liver tissue, causing the dysregulation of glucose metabolism [ 100 ]. Serum levels of miR-143 were significantly increased in MetS patients compared to the control and were found to be associated with the risk of developing insulin resistance, suggesting the possible downregulation of circulating miR-143 to prevent this clinical condition [ 101 ].…”
Section: The Role Of Liver-derived Mirnas In Metabolic Regulation And...mentioning
confidence: 99%